Uncovering the naked: the economic dimension of nakedness in the Hebrew Bible and the innovations of Isaiah 58 - Holt, Sarah G. (2024)
This study challenges the consensus that to "feed the hungry and clothe the naked" (Isa 58:7; Ezek 18:7, 16) represents a charitable ideal for the righteous. Through an interdisciplinary examination of the language of "nakedness" in the Hebrew Bible, it argues that the economic dimension of the Hebrew lexemesערום andערוה is more pervasive and significant than is generally recognised. An extensive word study with the assistance of comparative Semitic texts leads to fresh interpretations of Deut 24:1; 1 Sam 20:30; 2 Sam 6:11-23; Isa 20:4; and Job 1:21, and sheds light on the rhetorical function of the notorious personified city texts. A meticulous close reading of Isaiah 58 probes the social context of the text to identify "the naked." Through the additional analysis of three key postexilic texts (from Neh 5; Lev 25; Ezek 18), the study proposes that the original life setting of the motif, as it appears in Ezek 18, is the social obligation of providing for dependent close kin, quintessentially, one's elderly parents. Isaiah 58 constitutes a two-fold social innovation. It suggests that creditors have a social obligation to provide for those whose land they have seized as if they were dependent kin, since they all belong to the “household of Jacob.” It also calls for the abolition of a hypothetical legal instrument, theמטה (not "yoke," vv. 6, 9), whereby land pledged as security was acquired from defaulting debtors. It constitutes a rare example of a prophet’s call to justice demanding a specific amendment to legal-economic practice rather than effectively maintaining the status quo. As such, it presents an inspiring model for those fighting for a more equitable society today.